SCOPE AND POTENTIAL FOR INDIGENOUS TOURISM- AN ANALYTICAL STUDY IN WAYANAD, KERALA - SIBI.P.S AND G. ANJANEYA SWAMY
Tourism Industry has embraced many positive changes in the recent years. The conventional mass tourism centers have made way for new eco-friendly destinations that help sustainable tourism development. Tourism in the state of Kerala is going through such a phase as its focus shifts from the traditionally popular sites like Munnar, Thekkady, Alappey, Kovalam etc. to Wayanad, Varkala, Nelliyampathy, Bekkal, Wagamon etc. These are unspoilt eco-friendly destinations which need careful and sustainable approach to take Kerala tourism to higher levels in the decades to come. Wayanad is such an upcoming tourist destination which has created euphoria among thousands of tourists around the world in the last few years. The lush green nature and the presence of a large number of tribes make Wayanad a very sensitive area in ways more than one. As such, in this study, an attempt is made to unveil the indigenous tourism potential of Wayanad . The study focused mainly on indigenous tourism as a sustainable model for Wayanad. The field study focuses on various small scale community ventures and tribal villages to identify the place specific indigenous tourism products. The experts in the study area were interviewed and the inputs obtained were interpreted through content analysis. The results of the study bring to light the potential tourism market for Wayanad tourism. The experts‟ views point out the present tourism scenario in Wayanad and the major challenges faced by Wayanad tourism, especially indigenous tourism.